Work Shifts Affect Blood Pressure in Employees In Tegal Sari Mandala II Village - Siti Nur Azizah; Sheila Dhiene Putri (Buletin Farmatera, 2025)
Abstract: Work shifts are a work system that is widely applied in various work sectors to increase productivity. However, the implementation of this system can hurt workers' health, especially in terms of blood pressure. Based on data from Tegal Sari Mandala II Village, Medan City, it was found that there was an increase in the prevalence of hypertension in workers who worked shifts compared to workers who had fixed working hours. Hypertension in shift workers can be caused by circadian rhythm disruptions, increased cortisol levels, irregular sleep patterns, and higher stress levels. This study aims to determine the effect of work shifts on blood pressure in employees in Tegal Sari Mandala II Village. This study uses an analytical design with a cross-sectional method. The sample consisted of 100 randomly selected employees. Data was collected through blood pressure measurements using a digital sphygmomanometer. Data analysis was carried out using the Chi-Square test with univariate and bivariate methods to measure the relationship between work shifts and hypertension. The results showed a significant relationship between work shifts and hypertension incidence (p=0.001). Shift workers are more prone to hypertension than non-shift workers, with the prevalence of grade 2 hypertension being 14 employees in the shift group. Shift workers have a higher risk of hypertension than non-shift workers. Therefore, structured occupational health interventions, good sleep patterns, and education about stress management are needed to reduce the risk of hypertension in shift workers.